Effects of an Isotonic and a combination Isometric-Isotonic exercise programme upon push-up performance - Barker, J. W. (1972)
The effects of a repetition push-up exercise programme and a repetition combination isometric-isotonic push-up exercise programme upon muscular endurance as measured by maximum repetition of push-ups were studied. Thirty-four male subjects enrolled in a wrestling activity class were equated into three groups on the basis of maximum repetition push-up performance. Group 1 (N = 12) performed maximum repetition push-ups; Group 2 (N = 11) did maximum repetition combination isometric-isotonic push-ups; and Group 3 (N = 11) served as the control group. Subjects in Groups 1 and 2 performed their exercises, after which all subjects participated in wrestling activities. All subjects were retested six weeks later after the two experimental groups had been subjected to twelve exercise periods. Both experimental groups showed statistically significant improvements in maximum repetition push-up performance. There was not a statistically significant difference between the mean increases of the two experimental groups. Within the limits of this study the results indicated that muscular endurance may be improved at nearly the same rate by both repetition push-up exercises (isotonic) and repetition combination isometric-isotonic push-up exercises.